Pediatric Zirconia Crowns: A literature review - Okumuş, İrem; Akgün, Semih Ercan; Tekin, Bahar; Guler, Derya (Mesut TUZLALI, 2024)
Early childhood caries remains a problem that needs to be addressed by pediatric dentists and is a frequently encountered clinical situation. Zirconium-supported restorations, a material frequently used in adult dentistry practices, have also been used in pediatric dentistry practice in recent years. Prefabricated pediatric zirconium crowns (PZCs) are used as alternatives to stainless steel crowns (SCCs), which are widely used in pediatric dentistry because of their insufficient aesthetic properties. PZCs have superior aesthetic and physical properties and high biocompatibility. Full coronal restorations are preferred, especially in cases where it is not possible to compensate for the loss of material in the tooth with traditional methods, and are aimed at increasing the structural strength of the tooth. PZCs have found clinical use in pediatric dentistry applications due to their durability and hardness resistance against forces and being an aesthetic material compatible with tooth color. In this review, the introduction of PZCs in clinical use, their physical properties, application principles, parental satisfaction, relationship with surrounding tissues, importance of microleakage in long-term success, and current clinical and laboratory studies are included.

Erken çocukluk çağı çürükleri (EÇÇ), klinikte sıklıkla karşılaşılan ve çocuk diş hekimleri tarafından ele alınması gereken bir sorun olmaya devam etmektedir. Erişkin diş hekimliği uygulamalarında sıklıkla kullanılan bir materyal olan zirkonyum destekli restorasyonlar son yıllarda çocuk diş hekimliği pratiğinde özellikle EÇÇ’nin yönetilmesinde sıkça kullanılmaktadır. Prefabrik pediatrik zirkonyum kronlar (PZK), yetersiz estetik özellikleri nedeniyle çocuk diş hekimliğinde yaygın olarak kullanılan paslanmaz çelik kronlara (PÇK) alternatif olarak ortaya çıkmıştır. PZK'lar üstün estetik görünüme, fiziksel özelliklere ve yüksek biyouyumluluğa sahiptir. Tam koronal restorasyonlar özellikle dişteki madde kaybını geleneksel yöntemlerle telafi etmenin mümkün olmadığı durumlarda tercih edilmekte ve dişin yapısal dayanımının arttırılması amaçlanmaktadır. Dayanıklılığı, kuvvetlere karşı dirençleri ve diş rengi ile uyumlu estetik bir materyal olmaları nedeniyle pediyatrik diş hekimliği uygulamalarında klinik kullanım alanı bulmuştur. Bu derlemede PZK'ların klinik kullanıma girişi, fiziksel özellikleri, uygulama ilkeleri, ebeveyn memnuniyeti, çevre dokularla ilişkisi, uzun dönem başarıda mikrosızıntının önemi, güncel klinik ve laboratuvar çalışmalarına yer verilmiştir.
Pediyatrik Zirkonya Kronlar: Bir literatür derlemesi
Keywords: Paedodontics; Çocuk Diş Hekimliği